Weight management strategies in Middle-Aged Women (MAW): Development and validation of a questionnaire based on the Oxford Food and Activity Behaviors Taxonomy (OxFAB-MAW) in a Portuguese sample - Leitão, Mafalda; Hartmann-Boyce, Jamie; Pérez-López, Faustino R.; Marôco, João; Pimenta, Filipa (Frontiers in Psychology, 2023)
Background: The Oxford Food and Activity Behaviours (OxFAB) taxonomy systematize the cognitive-behavioural strategies adopted by individuals who are attempting to manage their weight. The present study aimed to 1) develop a questionnaire based on the OxFAB taxonomy, specifically adapted for Middle-Aged Women - the OxFAB-MAW - stage of life and sex which present a high incidence of obesity, 2) assess the psychometric properties of this tool, and 3) evaluate the discriminative power of the OxFAB-MAW (normal weight vs. obesity). Method: Overall, 1367 Portuguese middle-aged women between45-65 years old (M = 52.3, SD = 5.15) filled in a socio-demographic, health and menopause-related questionnaire, as well as the OxFAB-MAW. Results: Confirmatory Factor Analysis demonstrated an acceptable model fit (Comparative Fit Index=0.928, Tucker-Lewis Index=0.913, Root Mean Square Error of Approximation=0.072, and Standardized Root Mean Square Residual=0.054). Five domains with one item were grouped in other domains, also Weight Management Aids domain was also removed. The OxFAB showed factorial, convergent, discriminant and external validity, as well as composite reliability. Conclusion: The OxFAB-MAW questionnaire is a valid, reliable, and theory-driven tool for assessing weight management strategies in middle-aged women, being able to discriminate between clinical and non-clinical groups (normal weight versus obesity) in several domains. This instrument can be used to gather valid and reliable data, useful in both research and clinical settings (especially focused on structuring interventions and preventive obesity programs within this specific life cycle stage).